The Outcry of Parents of Drug Surrenderees: A Phenomenology - Regine A. Ramirez; Ariel A. Alamban (People and Behavior Analysis, 2026)
The pervasive impact of the Philippine government’s anti-drug campaign has placed significant emotional, social, and moral burdens on families. However, the voices of parents—who often carry the weight of stigma, fear, and uncertainty—remain largely unheard. In the Philippines, the growing problem of illegal drug use has deeply affected not only those directly involved but also their families—particularly parents—whose struggles often go unnoticed. Responding to this gap, this study explored the outcry of parents of drug surrenderers. Using a qualitative phenomenological approach, in-depth interviews were conducted with 14 parents in Laak, Davao de Oro, to capture their lived experiences. Thematic analysis revealed three major experiences: emotional turmoil, strength in adversity, and doing what is right. Coping mechanisms included remaining strong and discerning, providing unwavering love and support, and maintaining faith and trust in the Almighty—strategies that enabled them to endure the challenges of substance abuse within the family. Insights shared by participants emphasized perseverance, open communication, and hope in God. These findings highlight the resilience and determination of parents facing the repercussions of drug involvement in their families, underscoring the need for empathetic, culturally sensitive interventions. Recommendations include community-based support programs, peer groups, and educational initiatives to empower parents and strengthen their coping abilities.